Circular Interpolation using Siemens S7-1200 - Thepjit Cheypoca; Amata Luanpol; Virot Wuti (My University, 2023)
This article proposes a way to control the movement of the step motor drive to control the movement of the 3 axes using a programmable logic controller (PLC) working instead of a numerical controller (NC). The workpiece can be milled the way it is needed, but the ability to control peripherals is limited, as it is a specific control system used to move the desired position. But the limitation of smaller PLC is that there is no order used to move directly as a curve, so a higher level of PLC is required, so smaller PLC are used to program curves with circular interpolation methods [1] to enable the use of curved motion.
Keywords: Industrial Automation and Control Systems; Robotic Mechanisms and Dynamics